Pendekatan Spiritual Care Model terhadap Self-Perceived Health pada Lansia - Dian Ratna Elmaghfuroh; Susi Wahyuning Asih (The Indonesian Journal of Health Science, 2025)
The elderly face various physical, psychological, social, and spiritual challenges affecting their self-perceived health. The Spiritual Care Model approach is a holistic strategy that can improve the spiritual well-being and quality of life of older adults. This study aims to analyze the effect of the spiritual care approach on self-perceived health in the elderly at PSTW Bondowoso. This study used a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 58 elderly people with normal cognitive function criteria, who were selected using a purposive sampling technique. The intervention was conducted with structured spiritual activities. Data was collected using the self-perceived health questionnaire and analyzed using the Wilcoxon test. The results showed a significant improvement in the Self-Perceived Health (SPH) of the elderly after implementing the spiritual care model. Before the intervention, the majority of respondents 72.4% were in the low SPH category, and after the intervention, it increased to 79.3% in the good SPH category. The Wilcoxon test resulted in a p-value = 0.0001, indicating a significant effect between the spiritual care intervention and improved self-perceived health. The spiritual care approach proved effective in improving the self-perceived health of older adults through the provision of spiritual, emotional, and social support. The findings emphasize the importance of integrating spiritual aspects in gerontological nursing care to improve the holistic quality of life of older adults.